Using properties of proportion solve for x:

`(sqrt(x + 1) + sqrt(x - 1))/(sqrt(x + 1) - sqrt(x - 1)) = (4x - 1)/2`

Advertisement Remove all ads

#### Solution

`(sqrt(x + 1) + sqrt(x - 1))/(sqrt(x + 1) - sqrt(x - 1)) = (4x - 1)/2`

Applying componendo and dividendo

`(sqrt(x + 1) + sqrt(x - 1) + sqrt(x + 1) - sqrt(x - 1))/(sqrt(x + 1) + sqrt(x - 1) - sqrt(x + 1) + sqrt(x - 1)) = (4x - 1 + 2)/(4x - 1 - 2)`

`(2sqrt(x + 1))/(2sqrt(x - 1)) = (4x + 1)/(4x - 3 )`

Squaring both sides

`(x + 1)/(x - 1) = (16x^2 + 1 + 8x )/(16x^2 + 9 - 24x)`

Applying componedo and dividendo

`(x + 1 + x - 1)/(x + 1 - x + 1) = (16x^2 + 1 + 8x + 16x^2 + 9 - 24x)/(16x^2 + 1 + 8x - 16x^2 - 9 + 24x)`

`(2x)/2 = (32x^2 + 10 - 16x )/(32x - 8)`

`x = (16x^2 + 5 - 8x)/(16x - 4)`

`16x^2 - 4x = 16x^2 + 5 - 8x`

4x = 5

x = 5/4

Concept: Concept of Proportion

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads